MENDELEY: UNTUK MENINGKATKAN KEMAMPUAN MENULIS DOSEN - Arizal N; Wita Dwika Listihana; Nofrizal Nofrizal (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2018)
In a successful college cannot be forgotten the existence of this one factor is the lecturer. Lecturers are the key to success in universities to educate students and students to be useful for the nation and the nation in the future. Some of the lecturers' duties include teaching, research and community service often mentioned by Tri Darma Perguruaan Tinggi. Of the three obligations of a lecturer is asked to have the ability to write skills such as Reports, Theses, Theses, Dissertations, Books, Articles and others. However, to be able to write well it is necessary to practice continuously and know the tools to write one is the tool for the citation and bibliography. Therefore required tools/applications that can help lecturers to write citations and bibliography. Mendeley is an application that can be used to write citations and bibliography,but not all lecturers can use this application. Methods to improve the ability to write lecturers do with several stages of lecture training materials/workshops about the contents of the introduction of Mendeley applications and videos about the ease of using this application, Practice using Mendeley application, Provide an opportunity for participants to ask questions or discussions about the material submitted, Conducting a survey to evaluate is done by spreading Pretest & Posttest quizoner with success indicator of success level understanding of participants in this program is 80%. The result of this activity proves that the lecturer can improve his writing ability is very positive for the development of lecturers expertise in making scientific research work. Keywords:Quality of lecturer, Writing, Quote, References.